Oxidation of Benzylic Alcohols by Tris[Trinitrato (Ce(IV)] Papraperiodate in solvent Free Condition - Shirini, F.; Pourhabib, A.; Azadbar, M.R. (Asian Journal of Chemistry, 2010)
Tris[trinitratocerium(IV)] paraperiodate has been used for the oxidation of benzylic alcohols to their corresponding carbonyl com- pounds in solvent free condition with high yields.